1997
DOI: 10.1038/sj.jhh.1000423
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C and blood pressure–an overview

Abstract: Background: Laboratory and some epidemiological reported an inverse association with vitamin C intake. studies suggest that antioxidants, such as vitamin C,The two non-randomised and four randomised conare protective for cardiovascular disease. This protectrolled trials were all small. Of the randomised trials one tive effect may be mediated through blood pressure reported a significant decrease in BP, one a non-(BP). This is the first systematic review of epidemiologsignificant decrease and two were uninterpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
51
1
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(57 citation statements)
references
References 3 publications
2
51
1
2
Order By: Relevance
“…had extensive experience using these techniques, having done so in the discovery of the latch mechanism in the regulation of smooth muscle contraction [Dillon et al, 1981]. We were led to predict that if the ascorbate-adrenergic coupling did anything physiologically, it would produce a reduction in smooth muscle contraction, since a number of human studies had recently appeared showing that vitamin C supplementation lowers blood pressure [Bendich and Langseth, 1995;Ness et al, 1997;Nyyssonen et al, 1997;Bates et al, 1998]. Hindsight being, if not 20/20, at least a little better than foresight, we failed to note several phenomena.…”
Section: What Problem Does Our Discovery Solve?mentioning
confidence: 99%
“…had extensive experience using these techniques, having done so in the discovery of the latch mechanism in the regulation of smooth muscle contraction [Dillon et al, 1981]. We were led to predict that if the ascorbate-adrenergic coupling did anything physiologically, it would produce a reduction in smooth muscle contraction, since a number of human studies had recently appeared showing that vitamin C supplementation lowers blood pressure [Bendich and Langseth, 1995;Ness et al, 1997;Nyyssonen et al, 1997;Bates et al, 1998]. Hindsight being, if not 20/20, at least a little better than foresight, we failed to note several phenomena.…”
Section: What Problem Does Our Discovery Solve?mentioning
confidence: 99%
“…Epidemiologic studies have confirmed a strong inverse relationship between serum ascorbate levels and blood pressure [61][62][63]. Plasma levels of ascorbate are lower in hypertensive subjects (mean 40 umol/L) compared to normotensive controls (mean 57 umol/L) [ 64 ].…”
Section: An Alternative Hypothesis: the Loss Of Ascorbate And Rise Inmentioning
confidence: 96%
“…Numerous animal models have shown a key role for oxidative stress (present in the circulation, blood vessels, and kidney) in mediating hypertension [ 56 ]. Ascorbate administration also lowers blood pressure in many hypertensive animal models [58][59][60].Epidemiologic studies have confirmed a strong inverse relationship between serum ascorbate levels and blood pressure [61][62][63]. Plasma levels of ascorbate are lower in hypertensive subjects (mean 40 umol/L) compared to normotensive controls (mean 57 umol/L) [ 64 ].…”
mentioning
confidence: 94%
“…[8][9][10][11][12][13][14][15][16][17][18][19][20] In 1997 Ness et al concluded that there were too few clinical trials, and those reported at that time were generally too small and too varied to provide confirmatory evidence for a casual relationship. 21 This study was undertaken in order to evaluate the current clinical evidence that vitamin C supplementation lowers both systolic and diastolic blood pressure in hypertensive individuals, and to also review the hypothesized mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%